Incorporating transportation safety into land use planning: Pre-assessment of land use conversion effects on severe crashes in urban China. (February 2019) - Xie, Bo; An, Zihao; Zheng, Yiling; Li, Zhigang
Abstract: Severe crashes (SCs) have raised significant challenges to public safety in China. Given the prevalence of urban redevelopment, there is an urgent need to incorporate transportation safety into new-phase land use planning. This study presents an approach to pre-assess the traffic safety outcomes of land use conversions by investigating the association between land use conversions and variations in SCs in urban China. Generalized structural equation modelling (GSEM) was used to construct the hierarchical relationships among the SC frequency, land uses, and SC-related features. The Wald test was then employed to examine the reshaping of SC-related features and the SC frequency variation in land use conversions. The results showed that urban residential, commercial and business and mixed residential-commercial land uses had the highest SC risk exposure levels. A set of land use conversions oriented towards these three land uses were positively associated with the SC frequency and would universally drive the reshaping of SC-related features in the traffic volume, accessibility of destinations, and spatial variations in the population and employment at the traffic analysis zone level. These types of conversions were highly sensitive to the generation of mixed traffic flows, thereby leading to a higher risk of exposure to SCs. In contrast, land use conversions were less associated with the reshaping of zonal traffic speeds. The applicability of the proposed approach and the corresponding findings in supporting land use planning strategies for traffic safety improvements in transitional cities and urban China in particular was discussed. Highlights: Constructing the hierarchical relationships among the SC frequency, land uses, and SC-related features. Exploring the impact of land use conversions on severe crashes. Explaining the reshaping of severe crash-related features during the land use conversions. Presenting the potential applicability of pre-assessment in supporting land use planning for traffic safety improvements.